Análise ponderada de impacto ambiental (APOIA-NovoRural) em agricultura familiar no município de Mineiros - GO - Lopes, Karine (2020)
This research sought to evaluate the environmental performance of family farms of organic horticulture producers from Coopermin Cooperative members, in the municipality of Mineiros-GO, using a weighted environmental impact assessment system for Novo Rural activities (APOIA-NovoRural). The method consists of electronic spreadsheets established by Emater-GO, for family farming in the Midwest region. To this end, it carried out a document review in the agencies and official databases to obtain information on family farming in Mineiros-Goiás. Data from family farmers included in COOPERMIN and an organic producer were verified. The region of the three settlements studied is known in Pinga-Fogo and of these 6 plots in total were studied, two plots in each settlement. The results showed an acceptable general average, however, they pointed out the need to follow up on some indexes, particularly the economic one, with regard to the sale price of organic products and the inputs for their cultivation. Therefore, there is a need to adopt strategies in the studied properties related to social, economic and environmental aspects in order to strengthen the activity of organic production in southwest Goiás.